Prevalence and phylogenetic relationship among methicillin- and vancomycin-resistant Staphylococci isolated from hospital’s dairy food, food handlers, and patients - Zamkan, Mona Ahmed El; Mubarak, Asmaa Gaber; Ali, Alsagher Omran (Journal of Advanced Veterinary and Animal Research, 2019)
Objective: The aim of the present work was to investigate the mutual role that may be played by the served dairy food and food handlers in the transmission of methicillin- and vancomycin-resistant Staphylococcus aureus and coagulase-negative Staphylococci to patients who were hospitalized in Qena City, Egypt. Materials and Methods: A total of 210 samples including 90 dairy food samples which offered to the patients in the hospital, 60 nasal and hand swabs from food handlers working in the hospital, and 60 nasal and diarrheal swabs from patients suffering from diarrhea were investigated for the presence of coagulase-positive S. aureus and coagulase-negative Staphylococci, then isolates were screened for methicillin and vancomycin resistance phenotypically and genotypically. 16s rRNA gene sequencing was employed to construct the neighbor-joining tree. Results: Unlike food samples, both coagulase-positive S. aureus and coagulase-negative Staphylococci occurred in human samples. Methicillin- and vancomycin-resistant coagulase-negative Staphylococci could be detected in 41.7% & 20.8%, 68% & 31.9%, and 81.3% & 55.2% of isolates obtained from dairy food, food handlers, and patients’ samples, respectively. Whereas 81% & 64.3%, and 75.4% & 38.6% of coagulase-positive S. aureus obtained from food handlers and patients’ samples exhibited resistance to methicillin and vancomycin, respectively. Phenotypic resistance was confirmed molecularly through detection of mecA and vanA genes. Conclusion: A significant role can be played by food and food handlers in the transmission of methicillin- and vancomycin-resistant Staphylococci to patients, which has been proved in this study through the close phylogenetic relation between S. epidermidis isolated from food, food handlers, and patients’ diarrheal samples. J. Adv. Vet. Anim. Res., 6(4): 463-473, December 2019